Diagnostic Accuracy of Admission C Reactive Proteins in Predicting Severity of Acute Pancreatitis Keeping CT Scan as Gold Standard - Samid Ullah, Wajid Iqbal, Muhammad Ibrahim Saeed, Sana Hawa, Faisal Wasim Ismail (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Acute pancreatitis is common, with an alarming rise in the global incidence. The clinical course of AP is highly variable, ranging from mild, self-limiting symptoms to multiple organ dysfunction and/or death. Objective: To evaluate the diagnostic accuracy of admission C reactive proteins in predicting the severe acute pancreatitis keeping computed tomography as gold standard. Material and methods: This Cross-sectional study was conducted at Department of Gastroenterology, Aga khan hospital, Karachi from 19-06-2019 till 19-06-2020. Data was prospectively collected from patients after taking a verbal consent. 181 patients who met the diagnostic criteria were included. Quantitative data was presented as simple descriptive statistics giving mean and standard deviation and qualitative variables was presented as frequency and percentages. Sensitivity, specificity, positive and negative predictive values and diagnostic accuracy was calculated. Results: A total of 181 patients who met the inclusion and exclusion criteria were included in this study. Mean age, duration of symptoms, BMI, height, weight and CRP in our study was 49.48±10.36 years, 14.88±4.87 hours, 29.8±4.74 kg/m2, 146.5±10.41 cm, 78.9±8.58 kg and 110.9±28.54 mg/L. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of CRP for diagnosis of severe acute pancreatitis by taking CT scan as gold standard was found to be 88.8%, 81.5%, 94.7%, 65.9% and 87.2%. Conclusion: CRP it is an inexpensive alternative to the conventional severity assessment methods for the prediction of severity and outcome of patients with acute pancreatitis and can serve as an early indicator of the progression of acute pancreatitis into a serious state. Keywords: Severe acute pancreatitis, C reactive protein and CT scan.